Human leukocyte antigen‐A, ‐B, ‐C, ‐DRB1 and ‐DQB1 allele and haplotype frequencies in an Albanian population from Kosovo. (22nd June 2012) - Sulcebe, G.; Cuenod, M.; Sanchez‐Mazas, A.; Tiercy, J.‐M.; Zhubi, B.; Shyti, E.; Kardhashi, V.
Summary HLA‐A, HLA‐B, HLA‐C, HLA‐DRB1 and HLA‐DQB1 genotyping was performed in a sample of Albanian population from Kosovo. The comparison of the respective allele frequencies through Fst analysis resulted in a close relationship with the Albanians from Albania, the Bulgarians, FYROM Macedonians and Greeks, while the other neighbouring populations are slightly more distant.